Towards a sociology of art collections : the making of an art collection for the Irish Museum of Modern Art - Herrero, Marta (Trinity College (Dublin, Ireland). Department of Sociology, 2003)
This thesis offers an exploration into the making of an art collection for the Irish Museum of Modern Art in Dublin. Its aim is to set out a distinct methodology for a sociological approach to the study of art collecting. The theoretical framework selected for this purpose is a sociology of intellectuals, addressed through a theory of intellectual practices. It is based on Zymunt Bauman's and Pierre Bourdieu's writings on intellectuals and intellectual practices. Its main premise is that collecting is a form of intellectual practice, which takes place in a cultural field, that is, the field of contemporary art in Ireland. It seeks to answer whether intellectual practices legislate and /or translate. In addition, the thesis investigates the possibility that intellectual practices can contribute to cultural transformation.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin